Sistematización de la experiencia pedagógica en la escuela comunitaria “A luz del sol” en Ciudad Bolívar: una apuesta por la educación popular enfocada en el reconocimiento y apropiación de actividades de autogestión. (2022)
The present work is the result of the systematization of one where the project of the popular school A luz del sol was implemented, a pedagogical experience there the spaces of self-management and community construction were managed for the boys and girls of the sector, who actively participated and allowed that the school process will gain more and more strength and could manage apprentice activities Sierra Morena, aje and development in the Paraíso neighborhoods and From the town of Bogotá, Ciudad Bolívar you will find some of the experiences . Throughout this work, educational activities on urban agriculture, eco-artistic crafts, strengthening of community ties, among others, were carried out jointly and left learning, experiences and social interactions in the neighborhoods, consolidating self-management and community building.